Pengaruh Knowledge Management terhadap Peningkatan Kinerja UMKM dengan Kompetensi sebagai Variabel Moderasi - Wahid Wachyu Adi Winarto (Universitas Muria Kudus, 2020)
This study aims to analyze the effect of knowledge management consisting of knowledge implementing, knowledge creating, and knowledge sharing on the improvement of the performance of Small Medium Enterprises (SMEs). In addition, it is also to determine whether competence can moderate the knowledge management variable on the performance of SMEs. This study used data from 57 SMEs in Kabupaten Pemalang as sample. Data were analyzed using multiple linear regression analysis, t test and F test and for the moderation test using the MRA (Moderated Regression Analysis). From the results of the analysis, it was obtained that partial knowledge implementation, knowledge creating, and knowledge sharing have significant positive effects on the performance of SMEs. Simultaneously, knowledge management has a positive effect on the performance of SMEs. The result of moderation test using MRA shows that competence cannot moderate the effect of knowledge implementing, knowledge creating dan knowledge sharing on the performance of SMEs.Penelitian ini bertujuan untuk menganalisis pengaruh knowledge management yang terdiri dari knowledge implementing, knowledge creating, and knowledge sharing terhadap peningkatan kinerja UMKM. Selain itu juga untuk mengetahui apakah kompetensi dapat memoderasi variabel knowledge management terhadap kinerja UMKM. Sampel dalam penelitian ini adalah 57 UMKM di Kabupaten Pemalang. Data di analisis menggunakan analisis regresi linier berganda, t test, F test dan untuk tes moderasi dgunakan Moderated Regression Analysis (MRA). Dari hasil analisis diperoleh hasil secara parsial secara parsial knowledge implementing, knowledge creating, and knowledge sharing memiliki pengaruh positif signifikan terhadap peningkatan kinerja UMKM. Secara simultan, knowledge management juga memiliki pengaruh positif terhadap UMKM. Hasil test moderasi menggunakan MRA menunjukkan bahwa kompetensi tidak mampu memoderasi hubungan antara knowledge implementing, knowledge creating dan knowledge sharing terhadap kinerja UMKM.